Studying the Thermal Influence on the Vibration of Rotating Blades - Abbas Abbas Fadhil; Hamzah Adawiya Ali (Measurement Science Review, 2022)
Computing the vibrating characteristics of any machine or structure is a necessary process that should be performed by the mechanical engineers that work in engineering design field to avoid the collapse under different kinds of applied loads. One of these kinds of structures are the rotating blades, whereas this part is considered as an essential element in many rotating systems that are used in different fields of engineering, e.g., turbomachinery, turbofan, helicopters, etc. One of the biggest disadvantages that is realized in rotating blades is failure due to vibrations and unbalance. It is possible that vibrations significantly reduce the performance of rotating blades compared to standard design conditions. If these rotating blades continue to operate under these circumstances for sufficient time, then the status of these systems will be unstable. Finally, this will lead to collapse of the rotating blades. In this work, a new code was created from scratch, based on the finite element method, to determine the vibrational characteristics of the rotating blades, taking into consideration the effect of rotating speed and temperatures. The compound influence of thermal gradients and rotating speed on the vibrational response (frequencies) for different configurations of blade was studied deeply.